2018
DOI: 10.1051/matecconf/201815005068
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Teacher on Cooperative Learning

Abstract: Abstract. The participation of students in the process of learning is one of the keys to ensure effective learning outcomes either in terms of knowledge or skill. However, teacher-centred teaching methods which have been practiced in this country after so long avert students to fully engage in the learning process especially in a classroom. Various attempts have been made by the government to emphasize student's development in term of communication, creativity and innovation through the of process learning in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 1 publication
2
5
0
Order By: Relevance
“…Findings support the outcomes of the researches that reflected the positive attitude of the teachers towards collaborative task in educational contexts (e.g. Alias, Hussin, Mohamed Adnan, Othman, & Hussin, 2018;Ghaith, 2018;Prieto Saborit, Fernandez-Rio, Cecchini, Méndez-Giménez, & Méndez-Alonso, 2016). Besides, finding of this part are in line with similar studies that focused on the collaborative task implementation over educational contexts (e.g.…”
Section: Resultssupporting
confidence: 81%
“…Findings support the outcomes of the researches that reflected the positive attitude of the teachers towards collaborative task in educational contexts (e.g. Alias, Hussin, Mohamed Adnan, Othman, & Hussin, 2018;Ghaith, 2018;Prieto Saborit, Fernandez-Rio, Cecchini, Méndez-Giménez, & Méndez-Alonso, 2016). Besides, finding of this part are in line with similar studies that focused on the collaborative task implementation over educational contexts (e.g.…”
Section: Resultssupporting
confidence: 81%
“…In some cases, the play element caused the learners not to take the activity seriously thereby compromising class discipline (Warnich, 2016, Personal Archive, File 5, Sections B2, B4, B6). Some of these concerns resonate with the findings of prior research (Alias, Hussein, Hassan, Adnan, Othman & Hussein, 2018;Le, Janssen & Wubbels, 2018;Izci, 2016;Box, Skoog & Dabbs, 2015;Sach, 2015;Robinson, Myran, Strauss & Reed, 2014;Chiriac & Granström, 2012;Hämäläinen & Vähäsantanen, 2011), which indicated that teachers who shy away from interactive and collaborative assessment design methodologies tend to blame lack of teaching experience, lack of resources, limited knowledge of alternative assessment methods, and lack of self-confidence which, in turn, creates fear of loss of control in the classroom.…”
Section: Discussionmentioning
confidence: 77%
“…Numerous studies have been conducted on collaborative learning and its impact on EFL students in diverse contexts and settings. For example, Alias et al [42] discovered teachers' perceptions and employed collaborative learning in the teaching and learning processes. The results demonstrated that teachers had a favorable viewpoint on collaborative learning.…”
Section: Previous Studiesmentioning
confidence: 99%